2005
DOI: 10.1111/j.1365-3180.2005.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sampling methodologies for site‐specific management ofAvena sterilis

Abstract: The ability to manage weed infestations in a spatially precise manner requires efficient and accurate methods of mapping weed distributions. A study was conducted to compare four different ground-based methods for collecting georeferenced information on infestations of Avena sterilis in winter wheat and barley. Sampling was performed at harvest by scoring panicle density, either from the ground or from a combine, by counting the number of panicle contacts with a stick moved horizontally over the crop canopy by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Herbicide application maps were based on the prescription rules showed in Table 1. Limit values for A. sterilis infestation in site‐specific treatments were conservative, that some areas, especially buffer areas, would receive higher rates than those suggested by Barroso et al. (2005).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Herbicide application maps were based on the prescription rules showed in Table 1. Limit values for A. sterilis infestation in site‐specific treatments were conservative, that some areas, especially buffer areas, would receive higher rates than those suggested by Barroso et al. (2005).…”
Section: Methodsmentioning
confidence: 93%
“…Because of the relatively large year‐to‐year variation in yield loss responses (Torner et al. , 1991; Barroso et al. , 2005) and because of the fact that we were trying to define strategic approaches to weed control, a broad description of yield loss risks was considered more convenient than very specific descriptions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1992). Avena ludoviciana mapping studies conducted in winter cereal fields in central Spain have shown an aggregated pattern of this species in the absence of herbicide treatments (Barroso et al. , 2001; Ruiz et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that weeds are generally aggregated in patches within a field (Marshall, 1988;Wiles et al, 1992). Avena ludoviciana mapping studies conducted in winter cereal fields in central Spain have shown an aggregated pattern of this species in the absence of herbicide treatments (Barroso et al, 2001;Ruiz et al, 2002). This fact is important from the point of view of weed management.…”
Section: Introductionmentioning
confidence: 99%